Finance and Development, September 1972. (Finance and Development; Finance and Development, 1972)
This paper describes what is a 'World Bank Project.' The paper highlights that by the 1960s, the concept of a 'project' had already widened. Starting in the late 1950s, the World Bank began expanding its lending into new sectors; today, the Bank lends for a wide variety of projects in agriculture, education, population planning, tourism, telecommunications, and water supply in addition to projects for electric power, transportation, and industry. Agricultural lending, in terms of the number of projects, is now the single most important sector.